Patient Satisfaction of Telemedicine in Pediatric and Young Adult Type 1 Diabetes Patients During Covid-19 Pandemic - Marta Bassi; Marta Bassi; Marina Francesca Strati; Marina Francesca Strati; Stefano Parodi; Simone Lightwood; Clara Rebora; Francesca Rizza; Giuseppe d'Annunzio; Nicola Minuto; Mohamad Maghnie; Mohamad Maghnie (Frontiers Media S.A., 2022)
The aim of this study was to evaluate the satisfaction of the use of telemedicine and telenursing in children and young adults with Type 1 Diabetes and their families followed in the Regional Pediatric Diabetes Center of Giannina Gaslini Institute (Liguria, Italy). An anonymous survey form was administered to 290 patients (138 filled out by caregivers and 152 by patients). The questionnaire consisted of two parts: the first one included a series of questions related to the patient's personal and medical data; the second one was directed toward the satisfaction in the use of telemedicine and telenursing during Covid-19 pandemic. The data collected showed that 92.4% of the population was overall very satisfied with the quality of the service provided. Satisfaction was much higher especially in those who live outside of the province of Genoa (p = 0.017) and in those on insulin pump treatment (p = 0.037). Telemedicine and telenursing have an essential role in diabetology and are highly appreciated in our Center, where most patients prefer to continue regular follow-up via video-call as well as in person. Telenursing was also proved to be an effective and appreciated tool for educating and supporting patients using insulin pumps and glucose sensors.